2021
DOI: 10.3389/fgene.2021.799099
|View full text |Cite
|
Sign up to set email alerts
|

Integrative RNA-Seq and ATAC-Seq Analysis Reveals the Migration-Associated Genes Involved in Antitumor Effects of Herbal Medicine Feiyanning on Lung Cancer Cells

Abstract: Lung cancer is one of the leading causes of cancer-associated death in the world. It is of great importance to explore new therapeutic targets. Traditional Chinese medicine formula Feiyanning has been clinically administered in China for more than a decade and raised attention due to its anticancer effect in lung cancer. However, the underlying molecular mechanisms remain to be elucidated. In the present study, we carried out cellular and molecular assays to examine the antitumor activities and understand the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Open chromatin‐accessible regions have been found to contain cis‐regulatory elements and possibly modulate gene activity 30 . A study has pointed out that in NSCLC cells, the transcriptional activity of migration‐associated genes is downregulated using the Feiyanning formula treatment, which prolongs patient survival 31 . Therefore, we hypothesized that low ATAC‐seq signal is associated with a better immune response.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Open chromatin‐accessible regions have been found to contain cis‐regulatory elements and possibly modulate gene activity 30 . A study has pointed out that in NSCLC cells, the transcriptional activity of migration‐associated genes is downregulated using the Feiyanning formula treatment, which prolongs patient survival 31 . Therefore, we hypothesized that low ATAC‐seq signal is associated with a better immune response.…”
Section: Discussionmentioning
confidence: 96%
“…30 A study has pointed out that in NSCLC cells, the transcriptional activity of migration-associated genes is downregulated using the Feiyanning formula treatment, which prolongs patient survival. 31 Therefore, we hypothesized that low ATAC-seq signal is associated with a better immune response. In our study, patients in mirlncRNA cluster A had the lowest ATAC-seq signal (Figure 4A-D) and the best immunotherapeutic response (Figure 6F-H).…”
Section: Discussionmentioning
confidence: 99%
“…Images from at least 5 fields of each well were randomly selected and evaluated via Image Pro Plus 6.0 software. The experimental protocol was based on the previous studies with appropriately modified [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Traditional Chinese medicine formula Feiyanning has been clinically administered in China for more than a decade and raised attention due to its anticancer effect in lung cancer. Wang et al (2021) revealed the migration-associated genes involved in antitumor effects of herbal medicine Feiyanning on lung cancer cells using RNA-Seq and ATAC-Seq analysis. Recent works presented novel biomarkers in gastric cancer [8].…”
mentioning
confidence: 99%